Knowledge and use of emergency contraceptive methods and associated factors among female youth college students in Gondar city, Northwest Ethiopia, 2023 - Tigist Abewa; Abebaw Addis; Desale Bihonegn Asmamaw; Lakew Asmare; Tihtna Alemu; Fekade Demeke Bayou (BMC, 2024)
Abstract Background Proper use of emergency contraception can reduce unintended pregnancy and the risk of abortion. Despite this fact, there is a high rate of unwanted pregnancies among adolescents in Ethiopia. Therefore, determining the level of knowledge and use of Emergency contraceptives (EC) among female youth is important. Objective To assess Knowledge and use of EC methods and their associated factors among female college students in Gondar City, Northwest Ethiopia, 2023. Methods Institution-based cross-sectional study was employed among 814 female college students in Gondar City from April 15 to 28, 2023. A multi-stage sampling technique was applied to select the study participants. A self-administered questionnaire was used to collect the data. Epi-data version 4.6 and STATA Version 16, respectively, were used for data entry and analysis. A logistic regression model was fitted to identify factors associated with the outcome variables. Statistical significance was defined at a p-value < 0.05 and a corresponding 95% confidence interval. Result In this study, 46.2% [95% CI (42.78, 49.63%)] of the participants had adequate knowledge about EC and 26.1% [95% CI (22.82-29.74%)] of sexually active participants used EC. Muslim religion [AOR = 1.82: 95% CI (1.07, 3.09)], being single [AOR = 0.34: 95% CI (0.19, 0.63)], no discussion about reproductive health issues with their husband/partner [AOR = 0.43: 95% CI (0.27, 0.69)], year of study; second year [AOR = 1.63: 95% CI (1.03, 2.58)], third year [AOR = 1.80: 95% CI (1.11, 2.94)], and fourth-year students [AOR = 2.91: 95% CI (1.43, 5.96)] were significantly associated with knowledge about EC. While no discussion about reproductive health with their husband/partner [AOR = 0.09: 95% CI (0.04, 0.20)], monthly allowance [AOR = 3.03: 95% CI (1.54, 5.95)], perceive use emergency contraceptives as not a sin [AOR = 2.59: 95% CI (1.20, 5.60], knowledge about EC [AOR = 2.32: 95% CI (1.253, 4.29)] were associated with the use of EC. Conclusions Participants' knowledge and of use EC in the study area was low. Religion, years of study, marital status, monthly allowance, perception and knowledge, and having discussion were associated with the use of EC. School-based health education, and behavioral change communication interventions should be established and/or strengthened to address students in need of EC services.